Some Condition for Scalar and Vector Measure Games to Be Lipschitz - F. Centrone; A. Martellotti (International Journal of Mathematics and Mathematical Sciences)
We provide a characterization for vector measure games ν=f∘μ in pNA∞, with μ vector of nonatomic probability measures, analogous to the one of Tauman for games in pNA, and also provide a necessary and sufficient condition for a particular class of vector measure games to belong to AC∞.